Transforming Healthcare with Generative Artificial Intelligence: A Comprehensive Review - Arutjothi, G; Geetha, K; Nagapriya, J (International Journal of Computer Sciences and Engineering, 2025)
In today's world, the role of Artificial Intelligence (AI) has become very dominant in all sectors. It is destroying applications in various fields. It is used in the medical world in various ways as a very important field. It is being used in recent days to improve efficiency, predict diseases and improve patient outcomes. The rise of Generative Artificial Intelligence (GenAI) is one of the most important. This cutting-edge technology is using sophisticated models such as power converters and diffusion models to revolutionize various systems in the healthcare sector. This article aims to review on the transformative impact of generative AI applications on healthcare, highlighting their immense potential, identifying existing challenges, and outlining future research directions.